Peningkatan Kapasitas Pemasaran Produk Melalui Marketplace Dan Media Sosial Untuk UMKM - Bani Nurhakim; Cep Lukman Rohmat; Gilang Atha Anantyo Putra; Hikmaludin Bakhtiar Ilmi (AMMA : Jurnal Pengabdian Masyarakat, 2023)
This community service program aims to improve the knowledge and skills of Micro, Small, and Medium Enterprises (MSMEs) in utilizing digital marketing, marketplaces, and social media as effective product promotion strategies. The problems faced by MSME partners include low digital literacy, suboptimal use of marketplaces, difficulties in creating attractive promotional content, limited advertising budgets, and lack of confidence in using digital technology. Therefore, the solution offered in this program was through intensive training on digital marketing, marketplace utilization, social media strategies, and the creation of promotional content. The implementation methods involved identifying partner problems, preparing training modules, conducting hands-on workshops, as well as providing mentoring and monitoring. The results of this activity showed a significant increase in participants' understanding of digital marketing and managing marketplace accounts. Participants were able to independently create marketplace and business social media accounts, upload their products, and produce attractive promotional content. In addition, participants began to understand effective paid advertising strategies and were able to apply them in their product promotions. The outcomes of this program included active marketplace accounts, business social media accounts, quality promotional content, digital marketing training modules, and the formation of a digital MSME community as a platform for sharing experiences and support. This program is expected to encourage MSMEs to be more independent, expand their market reach, increase sales, and compete optimally in the digital era. The sustainability of this program is supported by continuous mentoring and online mentoring groups as a means of consultation and further development for MSME actors.